Preparation or provocation?: student perceptions of active shooter drills - Huskey, Michael G. (Criminal justice policy review, 2021)
Several highly publicized incidents of school violence in the past two decades have highlighted the importance of school safety and crisis preparation for students, parents, and school administrators. Although prior research has focused on the effectiveness of various security and crisis preparation measures, few studies have analyzed student perceptions of these policies. This study utilizes survey data collected from students at a public university in the southwestern United States to evaluate whether active shooter drills experienced in high school were related to negative student outcomes. Results show that experiencing an active shooter drill in high school was associated with significant increases in student fear, inflated perceptions of risk, and a decrease in perceptions of school safety. Implications for future research and policy initiatives regarding active shooter drills are discussed, specifically the need for increased transparency, standardization of drills, and addressing effective methods of implementing active shooter drills in schools.